An Examination of Changes to State Civic Education Requirements, 2004–2016. Issue 1 (1st January 2019) - Wilson, Jerry J.; Sadler, James; Cohen-Vogel, Noah; Willis, Connor
Abstract: Across the country, states are considering policies that support civic learning among youth. Recent initiatives at the state level have changed graduation requirements and state assessments around high school civics. These initiatives can be grouped into three types: coursework, assessments, and accountability. The first type, coursework, refers to whether a state's graduation requirements include a course in civics. The second, assessments, encompasses state requirements that students be assessed on civics or citizenship education. The third type, accountability, refers to whether a state's accountability system includes state assessments in civics or citizenship education. The purpose of this study is threefold: (1) to describe state policies in civics education and the variation in them among the American states, (2) to document the changes in state policies between 2004 and 2016, and (3) to help unpack the reasons behind changes to civics education policy among the American states. We find considerable variation in civics education policies across states, as well as substantial changes within states over time. Using event history analysis, we exploit the variation to examine the extent to which political, economic, and demographic factors inside a state as well as the actions of neighboring or regional states condition adoption of assessment policies. We find evidence that the proportion of Hispanic and black populations in a state are positively associated with adoption and discuss implications and areas for future research.